ESTETIKA JEAN FRANCOIS LYOTARD SEBAGAI "ESTETIKA RUANG KETIDAKSADARAN FREUDIAN' - Akhyar Yusuf Lubis (Jurnal Dimensi Seni Rupa dan Desain, 2013)
Abstract The term postmodern was born in the world of art. Now, though, the term has found a widesperad use in other field. Francois Loytard was a Philosoper who helped popularise the term among the academic community. He wrote an interesting , yet relatively unknown theory postmodern aesthetics. At a glance, Lyotard seemed to ignoe aesthetics theories in favour of merely enjoying works of art, for to him, art has to be able to mesmerize and make someone enjoy it. AbstrakIstilah posmodern lahir dari dunia seni dan pengguanaan istilah itu sekarang telah merambah ke berbagai bidang ilmu pengetahuan. Francois Lyotard, termasuk pemikir yang mempopulerkan istilah posmodern di lingkungan akademis. Francois Lyotard juga menulis tentang teori estetika posmodern yang sangat menarik, namun relatif belum dikenal